22. \( (x+1)^{2}-8(x+1)-9=0 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
Let’s dive into solving this quadratic equation! First, we can simplify our expression by making a substitution. Set \( y = x + 1 \). This transforms the equation into: \[ y^{2} - 8y - 9 = 0 \] Next, we can use the quadratic formula, \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 1 \), \( b = -8 \), and \( c = -9 \). Calculating the discriminant: \[ b^2 - 4ac = (-8)^2 - 4 \cdot 1 \cdot (-9) = 64 + 36 = 100 \] Now substitute back into the quadratic formula: \[ y = \frac{8 \pm \sqrt{100}}{2} = \frac{8 \pm 10}{2} \] This gives us two solutions: 1. \( y = \frac{18}{2} = 9 \) 2. \( y = \frac{-2}{2} = -1 \) Since \( y = x + 1 \), we can now return to \( x \): 1. \( x + 1 = 9 \implies x = 8 \) 2. \( x + 1 = -1 \implies x = -2 \) Thus, the solutions for the original equation are \( x = 8 \) and \( x = -2 \).